Cooperation in the Face of Conflict: Effects of Top Managers' Trust Beliefs in their Firms' Major Suppliers. (20th March 2019) - Holtgrave, Maximilian; Nienaber, Ann‐Marie; Tzafrir, Shay S.; Schewe, Gerhard
Abstract: As with any relationships, those between buying firms and their major suppliers are likely to experience situations of conflict. When facing such situations, top managers tend to approach conflict either cooperatively or competitively. However, when and why top managers tend towards cooperation or competition is far from clear. This study proposes a novel link between the theory of cooperation and competition and the discounting principle of attribution theory to argue that it is top managers' trust beliefs in their firms' major suppliers that influences their intended approach to conflict. Using survey data from 140 C‐level managers and business owners, the authors develop and test a model that differentiates between two attributional dimensions of trust (competence and goodwill) and the specific relational conditions that influence how these attributions operate. The results indicate that top managers' trust in their suppliers' competence and goodwill is, in fact, decisive in determining how they intend to approach conflict. Further, the authors demonstrate that a top manager's trust belief in the supplier's goodwill is of particular relevance in driving the top manager to cooperate in the face of conflict. However, this link seems to be contingent on the specific conditions of the buyer–supplier relationship in question.